Revolutionizing Lyme disease vaccination: a systematic review and meta-analysis of promising candidates - Tamanna, Sadia; Kim, Dong-Min (Frontiers in Cellular and Infection Microbiology, 2025)
The most prevalent vector-borne diseases in North America and Europe is still Lyme disease, which is caused by the bacterium Borrelia burgdorferi. As incidence rates rise, this poses a serious threat to public health. Since there is presently no vaccine for Lyme disease that is suitable for human use after the LYMErix vaccine was withdrawn in 2002 due to safety issues and insufficient adoption, there is an urgent need for an effective vaccination to protect at-risk populations. Numerous intriguing vaccine candidates have been developed as a result of advances in molecular biology and immunology; nevertheless, it is still unclear which candidate provides the best balance of durability, safety, and efficacy. The purpose of this meta-analysis and systematic review is to assess the safety and effectiveness of many Lyme disease vaccine candidates that are presently undergoing clinical trials. According to PRISMA guideline, the systematic review was performed, and the meta-analysis was performed using random-effect model. This study evaluates the efficacy of multiple Lyme disease vaccine candidates and identifies recombinant OspA-based formulations as the most promising by combining data from observational studies and randomized controlled trials. With an emphasis on OspA-based and multivalent vaccinations, we present comparative evaluations of immune responses, side effects, and long-term protection across vaccine platforms. This research is to help steer public health policy and vaccine development activities in the direction of a successful Lyme disease vaccine and emphasizes how certain vaccine candidates may lessen the impact of Lyme disease.